2015
DOI: 10.1089/jamp.2015.1225
|View full text |Cite
|
Sign up to set email alerts
|

In VitroDosing Performance of the ELLIPTA®Dry Powder Inhaler Using Asthma and COPD Patient Inhalation Profiles Replicated with the Electronic Lung (eLung™)

Abstract: Background: To evaluate the in vitro dose delivery characteristics of approved asthma and chronic obstructive pulmonary disease (COPD) therapies delivered via the ELLIPTA® dry powder inhaler across inhalation endpoints representative of the target patient population, using the Electronic Lung (eLung™) to replicate inhaler-specific patient inhalation profiles that were previously recorded in vivo.Methods: Selected profiles, representative of the range of inhalation endpoints achieved by patients with all severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 22 publications
2
30
0
4
Order By: Relevance
“…A frequent error of insufficient inhalation effort observed with Diskus Ò in the CRITIKAL study has also been observed with Ellipta Ò . In an in vitro study that replicated inhaler-specific patient inhalation profiles that were previously recorded in vivo using the Electronic Lung (eLung TM ), drug dose delivery via the Ellipta Ò DPI was consistent across the range of patient representative inhalation parameters for all therapies such as formoterol/ vilanterol, umeclidinium/vilanterol, and formoterol [49]. A recent study showed that patients with mild to very severe COPD could also generate sufficient inspiratory flows for optimum drug delivery via Ellipta Ò [50]; it should be noted that this may not always be true in real life.…”
Section: Ellipta òmentioning
confidence: 54%
“…A frequent error of insufficient inhalation effort observed with Diskus Ò in the CRITIKAL study has also been observed with Ellipta Ò . In an in vitro study that replicated inhaler-specific patient inhalation profiles that were previously recorded in vivo using the Electronic Lung (eLung TM ), drug dose delivery via the Ellipta Ò DPI was consistent across the range of patient representative inhalation parameters for all therapies such as formoterol/ vilanterol, umeclidinium/vilanterol, and formoterol [49]. A recent study showed that patients with mild to very severe COPD could also generate sufficient inspiratory flows for optimum drug delivery via Ellipta Ò [50]; it should be noted that this may not always be true in real life.…”
Section: Ellipta òmentioning
confidence: 54%
“…The inspiratory flow rate is an important inhalation profile parameter because of its direct influence on the dose delivery from most DPIs. The Ellipta device produces consistent dose delivery at flow rates over 30L/min [13,15] and this covers the inhalation rates across asthma and COPD disease severity, with even patients who suffer from very severe COPD able to generate an inspiratory effort of 41.6L/min whilst using the inhaler [15,16]. The particle size and fine particle fraction of the Ellipta inhalers vary by the medication delivered.…”
Section: Design Featuresmentioning
confidence: 99%
“…In vitro evaluation of drug delivery using patient inhalation profiles captured in vivo demonstrates mean delivery of 77-90% of the blister content depending on the device contents [15]. This results in a pulmonary fraction (Ex-throat dose) of 22.0-42.5% and a fine particle dose of 18.8-37.2%, again depending on blister contents.…”
Section: Design Featuresmentioning
confidence: 99%
“…Обладает средненизким сопротивлением [16]. Доля частиц оптимального размера, создаваемая уст ройством Эллипта, не зависит от объемной скорости потока на вдохе, по этому показателю Эллипта прак тически не отличается от своего предшественника -устройства Mультидиск.…”
Section: эллиптаunclassified
“…Доля частиц оптимального размера, создаваемая уст ройством Эллипта, не зависит от объемной скорости потока на вдохе, по этому показателю Эллипта прак тически не отличается от своего предшественника -устройства Mультидиск. Однако доля частиц опти мального размера у ингалятора Эллипта существен но выше, чем у Мультидиска, и составляет 30-36 % номинальной дозы [16] по сравнению с 20-25 % у Мультидиска [12].…”
Section: эллиптаunclassified